(untitled) (Medico Legal Update, 2020)
Background: Osteochondroma represents the most common benign tumor of bones and accounts for about 30-50 % of them. poor information’s in previous studies act on demonstration of the significance of atypical histological changes as a premalignant precursor in mature osteochondroma regardless of the cap thickness. In this study, the proliferative activity of cartilaginous cap will be studied in skeletally mature patients regardless of the cap thickness to demonstrate the independent significant of histological features in predicting the malignant potential in osteochondroma. methodology : cases of skeletally mature osteochondroma (78 case) were isolated and separated into sessile and pedunculated, then into G1(without suspicious histological features) and G2 ( with suspicious features), and stained with Ki- 67 . Data were analyzed using SPSS version 21and p value < 0.05 was considered as significant. Results: There was significant association between study groups and Ki 67 staining results, majority (75%) of patients with suspicious histopathological features presented with positive results of Ki 67 staining ( p value < 0.001). while there was no correlation between shape of lesion and histopathological features ( p value 0.662). Conclusion: atypical histopathological features can be regarded as independent factor with the other clinical data when considering the diagnosis of grade 1 chondrosarcoma.